(untitled) (East West Medical College Journal, 2026)
Background: Brucellosis is a pervasive zoonotic disease transmissible from vertebrate animals to humans. Despite dietary habits that typically contain unpasteurized milk, close contact with cattle during religious festivals and urban farming facilitates aerosolised transmission. The diagnosis is also challenging as it usually remains silent, and often patients come up with complications. This infectious disease has major public health implications and imposes considerable economic strain, especially in areas with insufficient food safety, hygiene and vet care. Case Presentation: A 38-year-old diabetic male presented with a four-month history of undulating fever, cough, and fatigue. He was previously misdiagnosed with seasonal flu. Clinical examination revealed hypotension (85/60 mmHg) and mild anaemia, but no organomegaly. While blood cultures were negative, a Triple Antigen Test showed significantly elevated titers for B. abortus (1:640) and B. melitensis (1:320). During hospitalisation, the patient developed chest pain; subsequent ECG changes (T-inversion in V1) and elevated Troponin-I (0.640 ng/ml) suggested acute myocarditis. He was successfully treated with oral doxycycline and intravenous gentamicin. Conclusion: This case underscores the emergence of human brucellosis in urban Bangladesh. Its non-specific, undulating symptoms make diagnosis challenging, posing a significant public health concern. EWMCJ Vol. 14, No. 2, July 2026: 245-250